DIGITAL EDITIONS IN CLASSICS: ELEMENTS OF GENRE IN THE PRODUCTION AND READING OF THE GREEK AND LATIN LANGUAGES - Ferreira, Anise [UNESP]; Blackwell, Christopher; Palladino, Chiara (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2020)
Digital editions in Classics have emerged as allies in breaking down barriers and facing challenges in teaching classical languages and cultures. The aim of this article is to highlight some specific features of digital editions in Classics, as possible genre elements in their digital production and reading, assuming they are a way of contributing to the mobilization of classical language learning and teacher training in the field. First, we describe the essential components in the process of a new digital edition of the Greek text of Oedipus Tyrannus, by Sophocles, prepared at Furman University for an undergraduate course. After that, we point out in what way digital edition annotations, in translation alignments, treebanking and geoannotations, as learning experiences, are potential development tools.
Keywords: Digital Classics; Teaching-learning Artifacts; Annotated Digital Editions; CITE